Hands-On Enterprise Java Microservices with Eclipse MicroProfile : Build and optimize your microservice architecture with Java /: Build and optimize your microservice architecture with Java. (2019) - Saavedra, Cesar; W. Rupp, Heiko; Mesnil, Jeff; Loffay, Pavol; Sabot-Durand, Antoine; Stark, Scott
No abstract available